The Use of Ambonesse Songs to Integrate English Learning and Culture Appreciation: a Classroom Action Research - Hursepuny, Johana; Rijoly, Helena M. (Pattimura University, 2021)
Foreign language class most often utilized learning materials with American or European background or from West Indonesian content. The English textbook used in schools rarely provides content material from where the students live (source/native Culture) such as Ambon, Maluku. Therefore, teachers must strive to provide an additional activity or materials that incorporate the local values and wisdom to the foreign language class. Ambonese songs are utilized as learning materials and classroom activities in an English Class. This classroom action research aimed to develop students’ vocabulary and engaging them with the local wisdom and values by rewriting and performing the Maluku songs in English. This paper will describe how to the Ambonese songs are used in the learning, the development of student’s vocabulary, students’ feedback, and some lesson learned from the process. The result shows that the teacher was satisfied with the process. Vocabulary was improved and retained and in overall students welcomed a different approach in learning English and learning about their culture as well.